Attention and Memory Biases as Stable Abnormalities Among Currently Depressed and Currently Remitted Individuals with Unipolar Depression - Gupta, Rashmi; Kar, Bhoomika R. (Frontiers in Psychiatry, 2012)
Background In the present study, we explored the possibility of the stability of attention bias and memory bias in currently remitted individuals with unipolar depression compared to currently depressed individuals with unipolar depression and never-depressed individuals. Methods The Emotional Stroop and autobiographical memory task were administered on 10 participants, who were currently depressed, currently remitted with unipolar depression, or never-depressed. In the emotional Stroop task (EST), the respondent’s task was to indicate the color of the ink of the positive, negative, and neutral words by selecting one of a series of colored blocks. In the autobiographical memory task (AMT), participants were presented with positive, negative, and neutral cue words. For each word, they were asked to report specific events from their life. Results Both the attention bias and memory bias exist in both the clinical groups. In EST, both currently depressed and currently remitted groups were slower to respond to negative words compared to neutral words. Unlike EST, in AMT both currently depressed and currently remitted groups were slower to respond to positive words compared to neutral words. Interestingly, the capacity to generate specific events for negative events was higher in both currently depressed and currently remitted groups. They were over-general in their memories of positive events. Importantly, the never-depressed group was specific in their memories of both positive and negative events of their life. Conclusions Our findings provide evidence for the stable existence of attention and memory bias in currently remitted individuals. This study has implications for the cognitive behavior therapy for depression to include modules to resolve the attention and memory bias toward negative thought and content, and to build strategies to overcome such biases.